2020
DOI: 10.1186/s12957-020-02064-7
|View full text |Cite|
|
Sign up to set email alerts
|

Outcome quality standards in advanced ovarian cancer surgery

Abstract: Introduction Advanced ovarian cancer surgery (AOCS) frequently results in serious postoperative complications. Because managing AOCS is difficult, some standards need to be established that allow surgeons to assess the quality of treatment provided and consider what aspects should improve. This study aimed to identify quality indicators (QIs) of clinical relevance and to establish their acceptable quality limits (i.e., standard) in AOCS. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Although perioperative management and surgical techniques are developing rapidly, postoperative complications may still be inevitable. A systematic review reported that the major complication rate was 23% for advanced ovarian cancer surgery [ 4 ]. Several findings have indicated that pleural effusion is the most common complication after cytoreduction for advanced stage epithelial ovarian cancer [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although perioperative management and surgical techniques are developing rapidly, postoperative complications may still be inevitable. A systematic review reported that the major complication rate was 23% for advanced ovarian cancer surgery [ 4 ]. Several findings have indicated that pleural effusion is the most common complication after cytoreduction for advanced stage epithelial ovarian cancer [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether anastomosis breakdown and other postoperative complications could be related to poor nutrition status is a hypothesis that cannot be ruled out. It should be taken into account that complications after surgery are related to surgical parameters but also depend on patient factors [ 21 ]. A study of patients with colorectal cancer resection showed no significant beneficial reduction in postoperative complications following nutritional supplementation, although patients who received whey protein supplementation 4 weeks before surgery had a mean improvement in functional walking capacity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complete cytoreductive surgery with platinum-based chemotherapy is the standard treatment for patients with AOC ( 7 ). The Society of Gynecologic Oncology and American Society of Clinical Oncology issued practice guidelines recommending NACT for patients with high perioperative risk or low likelihood of achieving optimal cytoreductive surgery ( 5 ). In our retrospective study, 757 AOC patients with optimal cytoreductive surgery had undergone NACT while 255 did not.…”
Section: Discussionmentioning
confidence: 99%
“…Standard of care for patients with advanced ovarian cancer (AOC) is primary cytoreductive surgery (PCS) followed by adjuvant chemotherapy ( 5 , 6 ). The leading prognostic factor in determining survival of patients with AOC is achievement of complete cytoreductive surgery with the aim of macroscopically complete resection of all visible tumor, followed by chemotherapy that includes carboplatin and paclitaxel ( 7 ).…”
Section: Introductionmentioning
confidence: 99%